Fabrication of biosensing surfaces using adhesive polydopamine. (20th December 2014) - Chu, Hunghao; Yen, Chun‐Wan; Hayden, Steven C.
<x xml:space="preserve">Abstract</x> Dopamine can be induced to polymerize on a variety of substrates, providing a robust and bioinspired surface coating that can be used to tune substrate surface properties and to sequester other species at the interface. We first exploit the facile nature of this surface modification procedure to generate an array of polydopamine that, in conjunction with fluorescent tags, provides the ability to detect multiple protein targets simultaneously and with great specificity. We then demonstrate the use of polydopamine as a matrix to confine gold nanoparticles at the surface of glass and graphene substrates. The nanoparticles (NPs) are used to template further gold nanoparticle growth in situ at the interface; subsequent calcination to remove the polydopamine matrix and sinter the NPs generates a highly active surface enhanced Raman scattering surface that allows for sensitive molecular detection. These varied uses in surface modification/biosensing demonstrate the utility of polydopamine as a functional surface modification for control of physical and electronic properties at the interface. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:299–306, 2015